A11 Induced pluripotent stem cells for basic and translational research on HD. (29th August 2012) - Mattis, VB; Svendsen, SP; Ebert, A; Svendsen, CN; King, AR; Casale, M; Winokur, ST; Batugedara, G; Vawter, M; Donovan, PJ; Lock, LF; Thompson, LM; et al.
Abstract : Background: The expression of mutant HTT leads to many cellular alterations, including abnormal vesicle recycling, loss of signalling by brain-derived neurotrophic factor, excitotoxicity, perturbation of Ca 2+ signalling, decreases in intracellular ATP, alterations of gene transcription, inhibition of protein clearance pathways, mitochondrial and metabolic disturbances, and ultimately cell death. While robust mammalian systems have been developed to model disease and extensive mechanistic insights have emerged, significant differences between rodent and human cells and between non-neuronal cells and neurons limit the utility of these models for accurately representing human disease. Human pluripotent stem cells can generate highly specified cell populations, including DARPP32-positive MSNs of the striatum, and provide a method for modelling HD in human neurons carrying the mutation. As it is caused by one single gene, HD is an ideal disorder for exploring the utility of modelling disease in induced pluripotent stem cells (iPSCs) through reprogramming adult cells from HD patients with known patterns of disease onset and duration. Aims: Generate iPSC lines from HD patients and controls and identify CAG-repeat expansion associated phenotypes. Methods/techniques: Through the efforts of an international consortium effort, 14 lines were generated, differentiated into neuronal populations and assessed for CAG-repeat dependent outcome measures. Results/outcomes: HD iPSC lines have reproducible CAG expansion–associated phenotypes upon differentiation, including CAG expansion-associated changes in gene expression patterns and alterations in electrophysiology, metabolism, cell adhesion, and ultimately an increased risk of cell death. While the lines with the longest repeats (HD180) showed a phenotype across all assays, those with shorter repeats (HD60) showed phenotypes in a specific sub set of assays. The most sensitive assay for establishing repeat dependent effects was found to be calcium responses to stress. Conclusions: This HD iPSC collection represents a unique and well-characterised resource to elucidate disease mechanisms in HD and provides a novel human stem cell platform for screening new candidate therapeutics. Funding: NIH, CHDI, CIRM.